Impact Editorial of Apex Journal of Business and Management for Celebrating Success - Mishra, A. K.; Prasai, Kul Prasad (Apex Journal of Business and Management, 2024)
The College's unique approach to promoting entrepreneurial characteristics among its graduates is instrumental in preparing them for successful careers in business. By fostering a culture of innovation, critical thinking, and ethical decision-making, Apex College equips its students with the skills necessary to excel in their chosen fields and contribute positively to society. Apex College's community engagement initiatives demonstrate the institution's dedication to addressing local needs and promoting social responsibility. The College's encouragement of entrepreneurial thinking and provision of resources, mentorship, and hands-on experience further contribute to the economic growth and job creation in Nepal. The Apex Journal of Business and Management, the College's flagship academic publication, serves as a vital resource for promoting research, education, and social change. The total sixty eight citations demonstrate referral of Apex Journal of Business and Management (AJBM) among scholars and academicians. Apex College's commitment to academic excellence, community engagement, and entrepreneurship positions it as a leader in the field of business education and a driving force for positive change in Nepal.